STUDI KOMPARASI KAPASITAS AXIAL BORED PILE DENGAN BERBAGAI FORMULA PADA PEMBANGUNAN SD ISLAM MAKARIMA KARTASURA - Dwi Ayu Aprilia; Sri Endang Wijaya Listiya Wati; Hartopo Hartopo; Totok Apriyanto (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2023)
The foundation is part of an engineering system that transmits the load supported by the foundation and its weight to and into the soil and rocks beneath it (Bowles, 1997). The Makarima Islamic Elementary School construction project was built using a 40 cm bored pile foundation. This study aims to determine the axial load transmitted to the foundation using SAP 2000 analysis and to determine the comparison of the foundation's bearing capacity based on the Sondir Test or CPT (Cone Penetration Test) data using various methods, namely based on the Mayerhoff, Schmertmann and Nottingham, and Aoki De Alencer methods. From the results of the SAP 2000 analysis, the axial force value was 162.7823 tons. From the Sondir data, the results of calculating the carrying capacity of a single pile foundation using the Meyerhoff method were 59.68 tons, the Aoki De Alencer method was 39.61 tons, and the Schmertman and Nottingham method was 43.54 tons, while the results of calculating the carrying capacity of the foundation group the Meyerhoff method was 256.89 tons, the Aoki De Alencer method was 170.5 tons, and the Schmeretman and Nottingham method was 187.43 tons. From the results of these calculations, the foundation is safe to use.